Etude de l’alimentation du magot Macaca sylvanus dans le site touristique des cascades d’Ouzoud (Maroc) - Abderrazak El Alami; Abderrahman Chait (Revue de Primatologie)
The Barbary macaque Macaca sylvanus is a generalist and opportunistic feeder with a highly flexible diet. Diets of Barbary macaque groups reflect the seasonal availability of different food categories. These abilities allow them to adapt to a wide range of habitats. The natural food of this primate include leaves, fruits, roots, bark, seeds, acorns, herbs, animal prey, bryophytes and lichen. In Morocco, several groups of Barbary macaques live in tourist sites, where they are affected by the presence of visitors providing food to them. Human food can become part of the diet of these groups and in few cases; macaques have become dependent on humans for survival. This work report data on the diet composition of the Barbary macaque group living in the tourist site of Ouzoud, in the central High Atlas of Morocco. We observed the group continuously from dawn to dusk during 2007-2012. We used instantaneous scan sampling at 15-min intervals. The diet of the study group includes essentially spontaneous and agricultural plants, human food, animal prey and lichens. On average, the study group spent 27% of the daily feeding time on eating leaves, 10% on fruits, 6% on seeds, 8% on roots and barks, 17% on herbs, 21% on human food and 11% on eating other items. The flora contributing to diet of the study group includes 87 species of angiosperms and gymnosperms, from theses 52 species are wild plants and 35 are agricultural plants. Conservation effort of Barbary macaques should consider the inclusion of human food in the diet of groups living in tourist sites.